A portable pencil-like immunosensor for point-of-care testing of inflammatory biomarkers - Nie, Rongbin; Huang, Jingwen; Xu, Xuexue; Yang, Li (Analytical and bioanalytical chemistry, 2020)
Portable devices for immunoassays are in high demand for point-of-care testing (POCT) of biomarkers. Here, we report a robust portable pencil-like immunosensor (PPS) platform for the determination of three inflammatory biomarkers including interleukin-6 (IL-6), procalcitonin (PCT), and C-reactive protein (CRP) in human serum samples. The PPS platform is composed of a unique pencil-like optical-fiber-based sensor, a reagent strip consisting of a series of pencil-cap-like wells, and a battery-powered photon counting detector for recording chemiluminescence. The PPS probe moves from well to well with a plug-into/out approach and goes through the immunoassay steps. Each fiber probe in the PPS platform can be sequentially used in up to 10 assays by simply propelling the intact probe out of the pencil body. The PPS platform is well-integrated into a portable suitcase-like device (32 cm × 23 cm × 11 cm) and is only 3 kg in weight. The sensor has good repeatability and can maintain 90% response after 14 days of storage at room temperature, showing its ability for assays in the field. The good linear relationship and efficient dynamic range with a limit-of-detection (LOD) of 1.05 pg/mL for IL-6, 10.64 pg/mL for PCT, and 29.40 ng/mL for CRP are obtained. The assay results are compared with clinical methods, and the findings confirm the high accuracy and precision of the proposed method. The proposed PPS platform is versatile and operable with minimal instruments and technical skills and simplifies the process of immune analysis, thus has great prospects for POCT of biomarkers. Graphical abstract